The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.25122/jml-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Oblique Coronal and Oblique Sagittal Magnetic Resonance Imaging (MRI) in Diagnosis of Anterior Cruciate Ligament (ACL) Tears

Abstract: Introduction Tears of the anterior cruciate ligament (ACL) are common among young athletes and diagnosis may be difficult especially in the young population. Therefore, finding a new method to increase the correct diagnosis is necessary. Materials and Methods This double-blind prospective observational study was conducted on 51 patients with suspected ACL rupture. In this study, in addition to the standard protocols, the oblique-sagittal and oblique-coronal MRI were assessed and used in three different metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The misdiagnosis rate of anterior cruciate ligament (ACL) tear of the knee joint is as high as 47% due to the confusion of high signal generated by synovial hyperplasia and partial volume effect on the standard MRI sequences 8 . A study revealed the evaluation of ACL tear by standard MRI sequences with additional oblique-sagittal plane showed high sensitivity and specificity 15 , 18 . Furthermore, another study using two additional oblique sequences (sagittal and coronal) to evaluate the ACL tear concluded that the use of oblique coronal and oblique sagittal MRI of the knee improved the diagnostic accuracy of the ACL tear 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The misdiagnosis rate of anterior cruciate ligament (ACL) tear of the knee joint is as high as 47% due to the confusion of high signal generated by synovial hyperplasia and partial volume effect on the standard MRI sequences 8 . A study revealed the evaluation of ACL tear by standard MRI sequences with additional oblique-sagittal plane showed high sensitivity and specificity 15 , 18 . Furthermore, another study using two additional oblique sequences (sagittal and coronal) to evaluate the ACL tear concluded that the use of oblique coronal and oblique sagittal MRI of the knee improved the diagnostic accuracy of the ACL tear 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The study using two additional oblique sequences (sagittal and coronal) to evaluate the ACL tear concluded that the usage of oblique coronal and oblique sagittal MRI of the knee improved the diagnostic accuracy of the ACL tear 19 . Furthermore, another study revealed the evaluation of ACL tear by standard MRI sequences with additional oblique-sagittal plane showed high sensitivity and specificity compared to a standard MRI protocol 18 . The results in these studies are similar to ours and we further found that our new modified DPP-TSO-Sag-FS-PDWI sequence can maximize the acquisition of ACL complete and true anatomical images and exclude the influence of anatomical differences between individuals, which is helpful to improve the authenticity and accuracy of ACL scanning images and to improve the diagnostic accuracy of ACL injury with its three grades.…”
Section: Discussionmentioning
confidence: 99%